Photopolymerization kinetics of bis-aromatic based urethane acrylate macromonomers in the presence of reactive diluent - Harikrishna, Reghunathan; Ponrathnam, S.; Rajan, C. R. (Progress in Organic Coatings, 2014)
The present work deals with the photopolymerization of bis-aromatic based urethane acrylate macromonomers in the presence of excess end capping agent as reactive diluent and estimation of their kinetic parameters. Formulations were made by independently homogenizing the macromonomers with photoinitiators of three different classes. Three different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using photo DSC under polychromatic radiation. The heat flows against time were recorded for all formulations under isothermal condition and the rates of polymerization, peak maximum times as well as the percentage conversions were estimated. It was observed that due to a longer timescale for reaction diffusion, formulations with macromonomer containing propoxylated backbone showed higher conversions than the corresponding ethoxylated analogue. The photopolymerization and kinetic estimations of the formulations including evaluation of kinetic model are discussed. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bimolecular termination model; kinetics; Macromonomer; Photopolymerization